Finding the best column for polar basic analytes across reversed-phase and hydrophilic interaction liquid chromatography - József Simon; Márton Kovács; Pál T. Szabó (Heliyon)
Background: The chromatographic measurement of polar molecules is often surprisingly complicated. On the one hand, the standard experiments use C18 columns, which is usually unsuitable. On the other hand, these types of molecules can behave vastly differently despite their similarities. Thus, finding the right chromatographic conditions is challenging. HILIC can be an obvious choice, but C18 is still used with suitable analytes. Comparing the two methods would be advantageous, but a numerical comparison can be problematic. Thus, a simple comparing and ranking system is needed and put to use to find the best method for the separation of polar basic molecules. Results: In this paper, nine columns with different stationary phases, from reversed-phase to hydrophilic interaction, are compared and ranked in gradient elution. The effect of pH was also considered. The measurements were repeated in acidic, near-to-neutral, and basic conditions. A straightforward system is developed to rank different stationary phases. Its foundation was peak shapes and resolutions. Every measurement condition with all the columns on the available pHs is evaluated by each property. The testing solution consisted of ten components, which aimed to cover a wide range of polar basic molecules. The comparison also focuses on these analytes. We highlighted which analyte is adaptable to different methods or which needed exclusive conditions. The resulting best column with the optimal conditions is presented and proven highly efficient for their separation. Significance: A straightforward comparison and ranking system is developed to test multiple chromatographic columns with different stationary phases, from reversed-phase to hydrophilic interaction in gradient elution, seeking the best method for separating polar basic molecules. Nine columns were compared in multiple conditions. The best setup resulting in the competition is presented in detail, which can be applied to a wide range of analytes.